Bimbingan Kelompok Sebagai Solusi dalam Mencegah Kekerasan Seksual (Studi Pada Santriwati Kelas XII Madrasah Aliyah Al-Falah Padang) - ahmad putra (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This study aims to find out the extent of understanding of female students in finding solutions to the threat of sexual violence that recently often occurs in educational institutions, especially in Islamic boarding schools. So with that, group guidance services are considered effective in revealing the understanding of female students with the aim of being able to protect themselves from threats that can come anytime and anywhere. This research is a fieldresearch using a qualitative approach. The subjects in this field research were 15 female students of class XII Madrasah Aliyah Padang. Collecting data through observation, and interviews (interviews). As for data analysis, that is by using descriptive qualitative which is data that has been obtained and then compiled and classified so that it can answer the questions above. The results obtained from the practice of this group guidance service are first, some female students have received news and information related to cases of sexual harassment that are rife in several Islamic boarding schools, second, some female students have made efforts to fend off sexual violence by participating in activities which are considered to be able to provide protection and a sense of security for personal safety, including participating in silat eskul and other activities.